UK Aviation: Carbon Reduction Futures. Final Report to the Department for Transport. - Morris, Joe; Rowbotham, Alex; Morrell, Peter; Foster, Andy; Poll, Ian; Owen, Bethan; Raper, David; Mann, Mike; Ralph, Malcolm (Cranfield University, 2009)
The objective of this study, commissioned by the Department for Transport, is to determine the scope for, and cost of actions that can be taken by, the UK domestic aviation sector to reduce its emissions of CO2. This involves estimating the cost of achieving CO2 abatement to help ensure that the most cost effective measures can be identified. For the purposes of this project UK domestic aviation refers to internal passenger flights within the UK only. The timeframe considered is the period 2007 to 2050. Given the timeframes involved and the evidence available, the costs and benefits of abatement options in this report are to be considered illustrative and represent broad orders of magnitude only. They are nonetheless indicative of the potential for abatement and relative costs.